In depth study of phenolic profile and PTP-1B inhibitory power of cold-pressed grape seed oils of different varieties. (15th January 2019) - Cecchi, Lorenzo; Innocenti, Marzia; Urciuoli, Silvia; Arlorio, Marco; Paoli, Paolo; Mulinacci, Nadia
Highlights: Pinoresinol was detected for the first time in cold-pressed grape seed oils. Total phenolic content ranged between 0.83 mg/kg to 15.16 mg/kg. Good correlation between total phenolic content and inhibitory power of PTP-1B. Pinoresinol, p -coumaric acid and quercetin give the major contribute to inhibition. Ethyl esters of gallic and caffeic acid were detected for the first time. Abstract: This paper investigates the phenolic composition of 17 monocultivar commercial cold-pressed grape seed oils. Chromatographic profiles showed the presence of more than 28 molecules, 11 of which were successfully identified by HPLC-DAD-MS-TOF and HPLC-FLD analysis. Pinoresinol, ethyl caffeate and ethyl gallate were detected for the first time in these oils. The total phenolic content ranged between 0.83 mg/kg for Viognier sample to 15.16 mg/kg for Merlot org sample. The detected ethyl esters can be suggested as markers to evaluate the intensity of fermentation in grape seeds before oil extraction, and to control the sensorial quality of the produced oils. In addition, the inhibitory power of these phenolic extracts against Protein Tyrosine Phosphatase 1B enzyme (PTP-1B), overexpressed in type-two diabetes, was investigated for the first time. Data highlighted a good correlation between total phenolic content and inhibitory power, with pinoresinol, p -coumaric acid and quercetin making the greater contributions.